Disability is not Inability : A Quest for Inclusion and Participation of People with Disability in Society - Nkomazana, F. (Fidelis); Amanze, James (Mzuni books, 2020)
This book is about people with disabilities (PWDs) and the extraordinary talents they have that can contribute towards the world economy generally and that of Southern and Central Africa in particular. The papers selected for this book were presented at an international conference that was held at the University of Botswana from 16th to 19th October 2018. The conference was held in order to address the injustices, discrimination and exclusion that people with disabilities face in their daily life. The papers discuss the need to train families and leaders in disability awareness, for clear national policies, the funding needed to address issues that affect PWDs, inclusive education, and the need to create a conducive environment and the implementation of policies, strategies and programmes. The book also points to the importance of sharing stories and experiences of success as a strategy of empowering PDWs.